Regularização de uma corda negra pelo método de Simpson-Visser - Lima, Arthur Menezes (2023)
In this work, a regular black string solution will be presented from the method used by Simpson-Visser to regularize the Schwarzschild solution. As in Simpson-Visser’s work, in this new black string solution, both a regular black hole and a wormhole can be represented by simply changing the value of a parameter “a” used in its metric. The regularization consists of changing the radial variable of the non-regular solution to add the parameter “a” in the new coordinate so that the new solution does not have singularity if a ̸ = 0. The analysis of the tensors and curvature invariants was carried out to verify the regularity of the solution, as well as the energy conditions of the system were analyzed, where it was verified that these will always be violated for the whole space, similar to the work of Simpson-Visser. An analysis of the thermodynamic properties of the regular black string was also carried out, in which the modifications generated by the original solution of the black string were evaluated, specifically, the Hawking temperature, entropy, its heat capacity, and the Helmholtz free energy. Finally, the possible stable or unstable circular orbits that could be possible for photons and massive particles were evaluated to compare the results with those of the non-regular black string, seeking to make a parallel with the work of Simpson-Visser.